Health impact assessment as an agent of policy change: improving the health impacts of the mayor of London's draft transport strategy. Issue 3 (13th February 2004) - Mindell, J; Sheridan, L; Joffe, M; Samson-Barry, H; Atkinson, S
Abstract : Objective: To increase the positive and mitigate the negative health impacts of the mayor's draft transport strategy for London. Design: A rapid prospective health impact assessment (HIA) of the penultimate draft of the strategy, using a review commissioned by the regional director of public health; an appraisal of congestion charging; and a participatory workshop. Two audits of changes were performed to assess the impact on policy of the HIA process. Setting: Regional government policy development. Intervention: Recommendations from the rapid HIA were fed back into the drafting process. Main outcome measure: Changes (a) between the penultimate draft and the draft for public consultation and (b) between that and the final mayoral strategy. Results: The draft transport strategy published for consultation differed in a number of respects from the previous version. Almost all the recommendations from the HIA were incorporated into the final strategy. Significant changes included promoting sustainable travel plans for workplaces and schools; giving priority to infrastructure and services that benefit London's deprived communities; increased emphasis on promoting walking and cycling and reducing reliance on private cars; and a commitment to track the health impacts of the final strategy and its implementation. Specific additions included re-allocating road space. Conclusion: HIA was successful in influencing the transport strategy for London, resulting in several improvements from a health viewpoint. HIA is an effective method both for bringing about significant change in policy proposals and in increasing policy makers' understanding of determinants of health and hence in changing attitudes of policy makers.